Social media usage, social media browsing, and sustainable purchasing attitude of consumers - Wahyu Ilham Pratama; Perengki Susanto (Operations Management and Information System Studies, 2023)
This study aims to analyze the effect of social media usage and social media browsing on sustainable purchasing attitudes among L'oreal consumers in Padang City with perceived environmental effectiveness as a moderating variable. This research was conducted using quantitative methods. The population in this study were all L'Oreal consumers in the city of Padang and the research sample was 272 respondents. This study uses a structural equation model (SEM) test with smart PLS 3.0 software. The results of this study include: (1) social media usage has a significant effect on sustainable purchasing attitudes and has a positive impact on sustainable purchasing behavior in the city of Padang. (2) social media browsing has a significant effect on sustainable purchasing attitudes. (3) perceived environmental effectiveness does not strengthen the relationship between social media usage and sustainable purchasing attitude. (4) perceived environmental effectiveness strengthens the relationship between social media browsing and sustainable purchasing attitudes.